Закономерности усадки при спекании однокомпонентных образцов из порошков Cu, Ni и Fe - Бондаренко, Н.А.; Мечник, В.А.; Супрун, М.В.; Дутка, В.А.; Панов, А.В. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2008)
Regularity of a shrinkage and shrinkage velocity are explored at caking of the singlecomponent samples from powders of cuprum, nickel and iron with the subsequent pressing. It is shown, that the forging pressure is the major factor influencing passing of given process, and activation energy and kinetic parameters characterize all its key moments.